Framework Investigation of Security Monitoring System for Production Line on IR 4.0 - Fadillah, Muhamad; Mulyana, Tatang; Wardhani, Rizal (International Journal of Integrated Engineering, 2020)
This paper presents an Investigative Framework for Security Monitoring Systems for Production Lines at IR 4.0. The framework consists of Raspberry Pi 3 as the main IoT processing module, four sensor there are RFID sensors, PIR Sensor, MQ2 Sensor, Magnetic Door Sensor. RFID is used to collect data that is being used in the area, PIR sensors to determine the state of the production floor where this sensor will measure the movement of the radius sensors, MQ2 sensors to determine the level of dangerous gas as quickly as cigarettes, methane gas that can cause fire on the production floor, Magnetic door sensor to determine the condition of the door on the production floor. This paper is for the framework of the cost and completeness of the system needs